2021
DOI: 10.4054/demres.2021.44.41
|View full text |Cite
|
Sign up to set email alerts
|

Marital dissolutions and changes in mental health: Evidence from rural Malawi

Abstract: Background 2 Objective 3 Context: Marital dissolutions and strategy in Malawi 4 Guiding research questions 5 Data and methods 5.1 Study details 5.2 Variables 5.3 Regression choices 5.4 HIV considerations and sensitivity analyses 6 Descriptive results 7 Multivariate results 8 Discussion 9 Limitations 10 Theoretical contributions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…The authors offer the possible explanations that divorce may empower women in ways that benefit their mental health, or that mentally healthy women experience more marriages because they are more likely to remarry. Meanwhile, results for men more closely mirror findings in Western settings: Spending more time outside of marriage is associated with worse mental health ( Myroniuk et al., 2021 ). On the other hand, another study in the same Malawian setting found that being formally married was associated with worse psychological well-being for men and women alike, and this was more pronounced among those in reproductive ages ( Clark et al., 2020 ).…”
Section: Conceptual Frameworkmentioning
confidence: 52%
See 3 more Smart Citations
“…The authors offer the possible explanations that divorce may empower women in ways that benefit their mental health, or that mentally healthy women experience more marriages because they are more likely to remarry. Meanwhile, results for men more closely mirror findings in Western settings: Spending more time outside of marriage is associated with worse mental health ( Myroniuk et al., 2021 ). On the other hand, another study in the same Malawian setting found that being formally married was associated with worse psychological well-being for men and women alike, and this was more pronounced among those in reproductive ages ( Clark et al., 2020 ).…”
Section: Conceptual Frameworkmentioning
confidence: 52%
“…However, the magnitude of associations between marital dissolution and self-rated health was weaker than anticipated, suggesting that people in such settings who survive to older ages may be selective on factors that make them more resilient against the potential negative impacts of marital dissolution ( Myroniuk, 2016 ). These studies offer important insight into the interrelationships between marriage and health in SSA settings, but they are limited in their sample sizes and their ability to distinguish between effects of widowhood versus divorce ( Clark et al., 2020 ; Myroniuk et al., 2021 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Early termination of first marriages implies prolonged exposure to these living arrangements, and most likely when the children affected were at young ages. Studies indeed suggest that an early experience of marital dissolution during the life course (Alter, Dribe, and Van Poppel 2007;McLanahan and Sandefur 2009;O'Flaherty et al 2016) and longer durations spent outside marriage following a union dissolution (Berntsen and Kravdal 2012;Dupre and Meadows 2007;Jennings, Chinogurei, and Adams 2022;Myroniuk, Kohler, and Kohler 2021) are associated with poorer health and well-being for individuals who experience these events, and the affected children. Therefore, it is important to know not only if a union dissolution is experienced over the life course but also when it occurs, whether the individual remarries, and how much time is spent in partnered versus unpartnered states.…”
Section: Introductionmentioning
confidence: 99%